Polystyrene with reduced flammability containing halogen-free flame retardants - Jankowski, P.; Kędzierski, M. (Polimery, 2013)
Additives that reduce the flammability of plastics were synthesized by a modification of expandable graphite (EG) using melamine salts (phosphate or cyanurate). Polystyrene (PS) was prepared by suspension polymerization of styrene in the presence of the obtained EG/melamine salt compounds. The resulting PS composites achieved horizontal FH-1 and vertical V-0 flammability ratings in the UL-94 burning test and the limiting oxygen index values increased by over 50 % compared with non-modified polystyrene. An advantageous effect of EG/melamine salt additives on the suppression of polystyrene combustion processes was also indicated by cone calorimetry and thermogravimetric analysis.